Components of state innovative policy and the mechanism of its implementation in the measurement of the world experience - Євтушенко, В. А.; Свєженцев, О. О. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2018)
The subject of the research is the modern innovative development in the conditions of application of the system of the state innovation policy instruments. The purpose is to systematize scientific views and analyze the criteria, components and directions of the state innovation policy, approaches to coordinating and regulatory role of the state in innovation policy and, on this basis, to make recommendations on the application of the components of an effective innovation policy of the country. The methodological basis for the article was the works of well-known foreign and Ukrainian economists on the subject of research, the results of the authors’ own research, analysis of the main international indicators of effective innovation development of the countries of the world. To achieve the goal, the following methods were used: dialectical, historical, logical, systemic, statistical and graphical. As a result of the research, the essence of innovation policy of the state and innovation and investment risks, factors hindering the innovative development of Ukrainian enterprises and functions of state innovation policy were determined.In order to develop and implement an efficient state innovation policy, a number of indicators that are components of the successful innovation policy of the country were analyzed, in particular, the ratio of the country’s expenditure on research and development as a percentage  of  GDP, the number of patents issued to the country’s citizens for innovations (within the country and abroad), and the same indicator but per million in the population of the country as well as the ratio of the share of high-tech and medium-tech products of the countries listed in the international innovative rating and the average interest rate of the country’s central bank. The concept of the state support for the development and implementation of innovations in the real sector of the economy is offered in this paper.